Cysteine 893 is a target of regulatory thiol modifications of GluA1 AMPA receptors. - Lotta von Ossowski; Li-Li Li; Tommi Möykkynen; Sarah K Coleman; Michael J Courtney; Kari Keinänen (PLoS ONE)
Recent studies indicate that glutamatergic signaling involves, and is regulated by, thiol modifying and redox-active compounds. In this study, we examined the role of a reactive cysteine residue, Cys-893, in the cytosolic C-terminal tail of GluA1 AMPA receptor as a potential regulatory target. Elimination of the thiol function by substitution of serine for Cys-893 led to increased steady-state expression level and strongly reduced interaction with SAP97, a major cytosolic interaction partner of GluA1 C-terminus. Moreover, we found that of the three cysteine residues in GluA1 C-terminal tail, Cys-893 is the predominant target for S-nitrosylation induced by exogenous nitric oxide donors in cultured cells and lysates. Co-precipitation experiments provided evidence for native association of SAP97 with neuronal nitric oxide synthase (nNOS) and for the potential coupling of Ca2+-permeable GluA1 receptors with nNOS via SAP97. Our results show that Cys-893 can serve as a molecular target for regulatory thiol modifications of GluA1 receptors, including the effects of nitric oxide.